ANALISIS AKTIVITAS ANTI BAKTERI EKSTRAK BENALU DARI BEBERAPA INANG TERHADAP PERTUMBUHAN BAKTERI PENYEBAB TYPHUS DENGAN METODE FUZZY LOGIC - Yulia Fatmi (RJOCS (Riau Journal of Computer Science), 2017)
Typhoid disease or better known as typhoid fever is a disease that can strike anyone, both children and adults, in Indonesia typhoid fever is a disease that causes high mortality rate. Treatment of typhoid fever itself can be done through a medical procedure. In addition there are also types of medicinal plants that can be used as an alternative treatment, one of which is Scurulla Sp. Its chemical content, efficacy / usefulness and side effects have not been studied scientifically. This study is focused to determine the inhibitory of the Scurulla Sp extract to the development of thypi monela cells that cause typhus. In this paper will discuss anti-bacterial activity based on three input variables i.e. the host of the Scurulla Sp, a solvent and as a test medium and output variable with no value and high.